Management accounting : theory and practice : a study of its principles and techniques with particular reference to Nigeria - Ola C.S. (Ibadan, Nigeria : Heinemann Educational Books, 1991)
The book discusses the fundamental tools of management accounting and the policy decisions which arise from the use of these tools both within the private and public sector.
Includes index
uaa 25/01/2019
Loans.
Keywords: Managment accounting; Nigeria